North on the wing : travels with the songbird migration of spring - Beehler, Bruce McP (Smithsonian Books, 2018)
In 2015, ornithologist Bruce M. Beehler set off on a solo backroads journey to trace the spring migration of songbirds from the southern border of the United States through the U.S. heartland and north into Canada. Traveling via car, canoe, bike, and on foot, Beehler followed migrant wood warblers and other songbirds from the Texas coast, up the Mississippi drainage to its headwaters in Minnesota and onward to the birds' nesting grounds in the north woods of Ontario. Engaging readers in the wonders of the spring migration, this book is a call to conserve, restore, and expand bird habitats to preserve them for the well-being of future generations of both birds and humans.